The Essential Role of Selenoproteins in the Resolution of Citrobacter rodentium-Induced Intestinal Inflammation - Nettleford, Shaneice K.; Zhao, Luming; Qian, Fenghua; Herold, Morgan; Arner, Brooke; Desai, Dhimant; Amin, Shantu; Xiong, Na; Singh, Vishal; Carlson, Bradley A.; Prabhu, K. Sandeep (Frontiers in Nutrition, 2020)
Enteropathogenic Escherichia coli (EPEC) leads to adverse colonic inflammation associated with poor resolution of inflammation and loss of epithelial integrity. Micronutrient trace element selenium (Se) is incorporated into selenoproteins as the 21st amino acid, selenocysteine (Sec). Previous studies have shown that such an incorporation of Sec into the selenoproteome is key for the anti-inflammatory functions of Se in macrophages and other immune cells. An intriguing mechanism underlying the anti-inflammatory and proresolving effects of Se stems from the ability of selenoproteins to skew arachidonic acid metabolism from pro-inflammatory mediators, prostaglandin E2 (PGE2) towards anti-inflammatory mediators derived from PGD2, such as 15-deoxy-12,14- prostaglandin J2 (15d-PGJ2), via eicosanoid class switching of bioactive lipids. The impact of Se and such a eicosanoid-class switching mechanism was tested in an enteric infection model of gut inflammation by C. rodentium, a murine equivalent of EPEC. C57BL/6 mice deficient in Se (Se-D) experienced higher mortality when compared to those on Se adequate (0.08 ppm Se) and Se supplemented (0.4 ppm Se) diets following infection. Decreased survival was associated with decreased group 3 innate lymphoid cells (ILC3s) and T- helper 17 (Th17) cells in colonic lamina propria of Se-D mice along with deceased expression of epithelial barrier protein Zo-1. Inhibition of metabolic inactivation of PGE2 by 15-prostaglandin dehydrogenase blocked the Se-dependent increase in ILC3 and Th17 cells in addition to reducing epithelial barrier integrity, as seen by increased systemic levels of FITC-dextran following oral administration; while 15d-PGJ2 administration in Se-D mice alleviated the effects by increasing ILC3 and Th17 cells. Mice lacking selenoproteins in monocyte/macrophages via the conditional deletion of the tRNA[Sec] showed decreased ILC3 and Th17 cells and poor resolution of inflammation following infection. Our studies indicate a crucial role for dietary Se in the protection against enteric infection via immune mechanisms involving epithelial barrier integrity.